(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Hyperprolactinemia is a common endocrine disorder that adversely affects reproductive and metabolic health. Recent findings emphasize the significant role of vitamin D and mineral metabolism in women with hyperprolactinemia, particularly in the context of comorbid hypothyroidism or pituitary microadenoma. Aim: To evaluate the levels of vitamin D, calcium, phosphorus, and magnesium, as well as parathyroid and calcitonin hormones in women with hyperprolactinemia, and to analyze their osteometabolic consequences.